ANALYSIS OF NAJMUDDIN AL THUFI'S CONCEPT OF THE SUPREMACY OF MASLAHAH AGAINST THE POSTULATES OF ISLAMIC LAW - Hannani Hannani (DIKTUM: Jurnal Syariah dan Hukum, 2021)
As the religion of rahmatan lil alamin, the arrival of Islam means a blessing and a gift to mankind. Therefore, the mujtahids agree that the formulation of Islamic law must refer to the interests of the wider community (mashlahah al-ummah). In its development, there are differences of opinion among scholars about whether maslahah should be prioritized over texts and ijma when there is a conflict. This study aims to analyze al Thufi's opinion about the supremacy of maslahah against other legal arguments. The method used is literature study to comprehensively analyze the concept of maslahah supremacy according to al Thufi. From the results of the study, it was found that al Thufi viewed maslhah as the strongest proposition compared to other arguments, but when al Thufi put maslahat first, it did not mean that at that time al Thufi ruled out texts, because al Thufi viewed the position of mashlaha as bayan takhshish.